Lived Experience of Emergency Health Care Utilization during the COVID-19 Pandemic: A Qualitative Study. Issue 6 (8th December 2021) - Smith, Erin; Hill, Michella; Anderson, Cameron; Sim, Moira; Miles, Alecka; Reid, David; Mills, Brennen
Abstract: Introduction: As the understanding of health care worker lived experience during coronavirus disease 2019 (COVID-19) grows, the experiences of those utilizing emergency health care services (EHS) during the pandemic are yet to be fully appreciated. Study Objective: The objective of this research was to explore lived experience of EHS utilization in Victoria, Australia during the COVID-19 pandemic from March 2020 through March 2021. Methods: An explorative qualitative design underpinned by a phenomenological approach was applied. Data were collected through semi-structured, in-depth interviews, which were transcribed verbatim and analyzed using Colaizzi's approach. Results: Qualitative data were collected from 67 participants aged from 32 to 78-years-of-age (average age of 52). Just over one-half of the research participants were male (54%) and three-quarters lived in metropolitan regions (75%). Four key themes emerged from data analysis: (1) Concerns regarding exposure and infection delayed EHS utilization among participants with chronic health conditions; (2) Participants with acute health conditions expressed concern regarding the impact of COVID-19 on their care, but continued to access services as required; (3) Participants caring for people with sensory and developmental disabilities identified unique communication needs during interactions with EHS during the COVID-19 pandemic; communicating with emergency health care workers wearing personal protective equipment (PPE) was identified as a key challenge, with face masks reported as especially problematic for people who are deaf or hard-of-hearing; and (4) Children and older people also experienced communication challenges associated with PPE, and the need for connection with emergency health care workers was important for positive lived experience during interactions with EHS throughout the pandemic. Conclusion: This research provides an important insight into the lived experience of EHS utilization during the COVID-19 pandemic, a perspective currently lacking in the published peer-reviewed literature.